Quantifying the impacts of expanding social protection on efficiency and equity: Evidence from a behavioural microsimulation model for Ghana - Robert Osei; Jukka Pirttilä; Pia Rattenhuber (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
A large informal sector is a challenge for developing countries building up social protection systems. Expanding social safety nets reduces poverty, but financing them can increase the tax burden, potentially reducing availability of formal sector jobs. This paper quantifies impacts on income distribution and efficiency of expanding developing countries' social protection. Results from a new tax-benefit microsimulation model for Ghana are combined with the extensive margin elasticity of the share of formal work with respect to the tax wedge on formal labour. Estimated formality elasticity is modest but statistically significant; therefore the distributional gains of expanding cash-transfer programmes are considerable, even taking into account behavioural impacts.
Keywords: H23; H31; O12; 330; developing countries; social protection; taxation; microsimulation